Ireland in focus : film, photography, and popular culture - Flannery, Eóin; Griffin, Michael J.; Graham, Colin, 1967- (Irish studies (Syracuse, N.Y.), 2009)
Ireland in Focus is the first book to address the diverse range of visual representations of national and communal identity in Ireland.